2022
DOI: 10.3390/bs12060178
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Serotonergic Activity and the Serotonin Content in Serum and Platelet, and the Possible Role of the Serotonin Transporter in Patients with Depression

Abstract: According to the monoamine hypothesis, the development of depression is associated with dysfunctions of the serotonergic system. Alterations in the serotonin transporter gene (5-HTTLPR), the serotonergic activity in the brain, and the content of serotonin (5-HT) have been related to depression and were examined separately by previous studies. This study investigates these parameters in 89 depressed patients and 89 healthy participants. We investigated the serotonergic activity measured by the loudness dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…The neurochemical underpinnings of LDAEP suggest that ECT should lead to a reduction in serotonergic tone within the primary auditory cortex, but this assumption is subject to debate. Studies on the relationship between LDAEP and serotonergic activity have harbored conflicting evidence and perspectives (19, 24, 52, 53). While numerous studies have found that the LDAEP is sensitive to acute changes in serotonergic activity, such as following administration of serotonergic-reuptake inhibitors, other studies have presented contrasting findings (54, 55, 56, 57, 58, 59, 60).…”
Section: Discussionmentioning
confidence: 99%
“…The neurochemical underpinnings of LDAEP suggest that ECT should lead to a reduction in serotonergic tone within the primary auditory cortex, but this assumption is subject to debate. Studies on the relationship between LDAEP and serotonergic activity have harbored conflicting evidence and perspectives (19, 24, 52, 53). While numerous studies have found that the LDAEP is sensitive to acute changes in serotonergic activity, such as following administration of serotonergic-reuptake inhibitors, other studies have presented contrasting findings (54, 55, 56, 57, 58, 59, 60).…”
Section: Discussionmentioning
confidence: 99%
“…However, statistical analysis revealed a positive, significant correlation between serotonin level and WBC, and the platelet count. It is known that platelets only transport serotonin produced outside bone marrow by enterochromaffin cells, but are unable to synthesize it [ 18 , 19 ]. Therefore, our findings may confirm the results of studies on the in vivo synthesis of serotonin by its precursors located in bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…The serotonergic activity in the brain was measured with the noninvasive LDAEP method. The performance and instructions of the LDAEP (cortical and source) can be taken from Obermanns et al (2022).…”
Section: Measurements Of the Serotonergic Activity In The Brain (Loud...mentioning
confidence: 99%
“…In a previous study, compared to healthy participants, we examined the relationship between serotonergic activity (cortical: patients 0.256 ± 0.186/healthy participants 0.252 ± 0.119; p = .855) and the concentration of serotonin in the peripheral blood (serum (patient: 230.9 ± 326.0 ng/mL/healthy participants: 773.8 ± 646.0 ng/mL; p < .001)/platelet (patient: 1113.9 ± 964.1 10 9 /Thr/healthy participants: 2008.8 ± 1026.4 10 9 /Thr; p < .001)) in patients with depression (see Obermanns et al, 2022). Concerning the CNR1 gene, there was a difference among the homozygote GG carriers, the AA allele genotype carriers, and the BDI-II in the group of healthy participants.…”
Section: Genotyping and Differences Between The Genotypesmentioning
confidence: 99%